2009
DOI: 10.1088/0004-637x/709/1/251
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of the Accretion Disk in the Accretion Disk Corona X-Ray Binary 4u 1822–371 at Optical and Ultraviolet Wavelengths

Abstract: The eclipsing low-mass X-ray binary 4U 1822-371 is the prototypical accretion disk corona (ADC) system. We have obtained new time-resolved UV spectroscopy of 4U 1822-371 with the Advanced Camera for Surveys/Solar Blind Channel on the Hubble Space Telescope and new V -and J-band photometry with the 1.3-m SMARTS telescope at Cerro Tololo Inter-American Observatory. We use the new data to construct its UV/optical spectral energy distribution and its orbital light curve in the UV, V , and J bands. We derive an imp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
60
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(72 citation statements)
references
References 39 publications
8
60
0
Order By: Relevance
“…UV spectra of X-ray binaries can generally be well fitted with continuum models, with emission lines like Mg II sometimes visible, but they usually produce a small amount of flux compared to the continuum in the UV (Hynes et al 1998Hynes & Haswell 1999;Bayless et al 2010). Small irregularities in the UV spectral energy distribution could therefore be due to the presence of prominent emission lines, but UV spectroscopy of X-ray binaries has shown that these usually make only a smallto-negligible difference to the continuum, and hence broadband UV filter fluxes.…”
Section: Contamination From Field Stars and Emission Linesmentioning
confidence: 99%
“…UV spectra of X-ray binaries can generally be well fitted with continuum models, with emission lines like Mg II sometimes visible, but they usually produce a small amount of flux compared to the continuum in the UV (Hynes et al 1998Hynes & Haswell 1999;Bayless et al 2010). Small irregularities in the UV spectral energy distribution could therefore be due to the presence of prominent emission lines, but UV spectroscopy of X-ray binaries has shown that these usually make only a smallto-negligible difference to the continuum, and hence broadband UV filter fluxes.…”
Section: Contamination From Field Stars and Emission Linesmentioning
confidence: 99%
“…Initially, Mason & Cordova (1982) derived an inclination angle between 76 • and 84 • fitting the light curve of X1822-371 in the infrared band. The modulation of the light curve is generally explained with the presence of a geometrically thick disc whose height varies depending on the azimuthal angle and occults part of the X-ray emission (White & Holt 1982;Mason & Cordova 1982;Hellier & Mason 1989;Bayless et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…1.8 × 10 −8 M yr −1 for a neutron star of 1.4 M ), suggesting that the mass transfer has to be highly non-conservative, with the neutron star accreting at the Eddington limit and the rest of the transferred mass expelled from the system. Bayless et al (2010), studying the optical and UV data of X1822-371, derived the new optical ephemeris for the source, finding a rapid change of the orbital period with P/Ṗ = (3.0 ± 0.3) × 10 6 yr, similar to the value of the recent X-ray ephemeris of X1822-371 obtained by Burderi et al (2010). Bayless et al (2010) showed that the accretion rate onto the neutron star should be 6.4 × 10 −8 M yr −1 in a conservative mass transfer, suggesting again a highly non-conservative mass transfer.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations